Lithium supplement agent and preparation method thereof, positive pole piece, battery and electric equipment
By adding hypoxic compounds to the coating layer of lithium supplement agent, the problem of increased gas production in lithium-ion batteries during lithium supplementation is solved, and the effect of reducing gas production and extending battery life is achieved.
Patent Information
- Application Number
- CN202411555645.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion batteries will have side effects during the lithium replenishment process, resulting in increased battery gas production and affecting the battery's service life and performance.
The reduced hypoxic compounds are added to the coating layer of the lithium supplement agent, and the released oxygen is extracted through the negative pressure process, and the residual reactive oxygen is consumed in the high-temperature storage section to reduce the catalytic decomposition of the electrolyte.
It effectively reduces the gas production of lithium-enhancing batteries, reduces the side reactions of the batteries, extends the service life of the batteries and improves its performance.
Smart Images

Figure CN119812325A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and specifically to a lithium supplement and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Lithium-ion batteries have the characteristics of high operating voltage, high specific energy, small size, light weight, and long cycle life, making them the focus of competition in the development of the automotive industry. With the continuous development of lithium-ion batteries in the fields of portable electronic devices, electric bicycles and electric vehicles, the requirements for lithium-ion battery performance such as energy density are getting higher and higher.
[0003] The loss of lithium is the direct cause of the attenuation of battery performance. At present, the lithium source consumed during the battery charging and discharging process can be supplemented by replenishing lithium in the positive electrode, thereby improving the energy density and cycle life of the battery. The commonly used lithium supplements are some lithium-rich oxides. These lithium-rich oxides release lithium ions during battery formation to make up for the efficiency loss during the first charge and discharge of the negative electrode. However, the lithium supplement will produce side reactions during lithium supplementation, resulting in increased gas production in the battery, which is not conducive to the use of the battery. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a lithium supplement agent and a preparation method thereof, a positive electrode plate, a battery and an electrical device. The lithium supplement agent of the present application is used in a battery to reduce the gas production of the lithium supplement battery.
[0005] The first aspect of the present application provides a lithium supplement. According to an embodiment of the present application, the lithium supplement is characterized by comprising:
[0006] An inner core, the inner core comprising a lithium-rich material;
[0007] The coating layer is coated outside the inner core, and the coating layer includes an oxygen-deficient compound.
[0008] The present application proposes to add an oxygen-deficient compound with reducing properties to the coating layer of the lithium supplement. During the formation process of the lithium supplement battery, the released oxygen can be pumped out by the negative pressure process, and the active oxygen remaining in the system will be consumed by the oxygen-deficient compound in the coating layer in the subsequent high-temperature storage stage. This is because the oxygen-deficient compound has a stronger reducing property than the electrolyte, and can compete with the electrolyte and capture catalytic factors such as active oxygen in the system, thereby reducing the catalytic decomposition and gas production of the electrolyte.
[0009] According to the embodiments of the present application, the above lithium supplement may also have the following additional technical features:
[0010] In some embodiments of the present application, the oxygen-deficient compound includes at least one of an oxygen-deficient metal compound and an oxygen-deficient non-metal compound.
[0011] In some embodiments of the present application, the oxygen-deficient metal compound includes at least one of Al2O 3-x , MgO 1-y and TiO 2-z ; wherein, 0 < x < 3, 0 < y < 1, 0 < z < 2; and / or, the oxygen-deficient non-metal compound includes SiO 2-a ; wherein, 0 < a < 2.
[0012] In some embodiments of the present application, based on the lithium-rich material, the mass percentage content m1 of the oxygen-deficient compound satisfies: 0 < m1 ≤ 10%.
[0013] In some embodiments of the present application, based on the lithium-rich material, the mass percentage content m1 of the oxygen-deficient compound satisfies: 0.1% < m1 ≤ 5%.
[0014] In some embodiments of the present application, the D50 of the oxygen-deficient compound is 20 nm to 200 nm; and / or, the D 50 of the lithium-rich material is 1 μm to 20 μm.
[0015] In some embodiments of the present application, the lithium-rich material includes a binary lithium compound or a ternary lithium compound.
[0016] In some embodiments of the present application, the lithium-rich material includes at least one of Li5FeO4, Li2NiO2, Li2O2 and
[0017] In some embodiments of the present application, the coating layer further includes a conductive material; the conductive material includes at least one of a conductive carbon material and a conductive non-carbon material.
[0018] In some embodiments of the present application, the water contact angle of the conductive material satisfies 90° ≤ θ ≤ 160°.
[0019] In some embodiments of the present application, based on the lithium-rich material, the mass percentage content m2 of the conductive material satisfies: 0 < m2 ≤ 10%.
[0020] The second aspect of the present application provides a method for preparing a lithium supplement agent, including:
[0021] Mixing and processing raw materials including a lithium-rich material and an oxygen-deficient compound, and heat-treating the mixture to obtain a lithium supplement agent.
[0022] The preparation method of the lithium supplement provided by the present application can be prepared by mixing, which is simple to operate and low in cost. The lithium supplement prepared by the present application contains an oxygen-deficient compound in the coating layer, which has a stronger reducing property than the electrolyte components, and can consume the active catalytic factors such as active oxygen generated by the lithium supplement in the formation stage and the high-temperature storage stage, thereby reducing the side reactions between the electrolyte and the lithium supplement, and further reducing the gas production.
[0023] In some embodiments of the present application, the preparation method includes: the step of mixing a lithium-rich material and an oxygen-deficient compound to obtain a mixture, further comprising adding a conductive material.
[0024] In some embodiments of the present application, the step of mixing the raw materials including the lithium-rich material and the oxygen-deficient compound is further subjected to heat treatment; the heat treatment control parameters include:
[0025] The heat treatment temperature is 20° C. to 200° C., and / or the heat treatment time is 1 h to 6 h.
[0026] In some embodiments of the present application, the anoxic compound is prepared by the following method:
[0027] A metal oxide or a non-metal oxide is mixed with a reducing agent and subjected to annealing to obtain an oxygen-deficient compound; wherein the annealing parameters include at least one of the following:
[0028] (a) Annealing temperature is 500°C to 1000°C;
[0029] (b) Annealing time is 6h to 15h;
[0030] (c) Annealing is carried out under an inert atmosphere.
[0031] The third aspect of the present application proposes a positive electrode plate, comprising the above-mentioned lithium supplement agent, or comprising the lithium supplement agent obtained by the above-mentioned preparation method.
[0032] The positive electrode plate provided in the present application, comprising the above-mentioned lithium replenishing agent, exhibits a good lithium replenishing effect and is beneficial to reducing gas production.
[0033] In some embodiments of the present application, the positive electrode sheet further includes a positive electrode active material; the positive electrode active material includes LiFePO4 and LiNi c Co d Mn 1-c-d O2, wherein at least one of 0.3≤c<1, 0≤d≤0.5.
[0034] The fourth aspect of the present application proposes a battery, comprising the above-mentioned positive electrode plate.
[0035] The battery provided in the present application includes the above-mentioned positive electrode plate, produces less gas and exhibits good capacity.
[0036] The fifth aspect of the present application proposes an electrical device including the above-mentioned battery.
[0037] The electrical equipment provided in this application has good safety performance.
[0038] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments with reference to the following drawings.
[0041] 11 is the core, and 22 is the cladding layer.
[0042] Figure 1 A schematic diagram of a lithium supplement according to an embodiment of the present application is shown. DETAILED DESCRIPTION
[0043] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0044] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0045] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.
[0046] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0047] At present, the commonly used lithium replenisher is a lithium-rich metal oxide, such as Li5FeO4, Li2NiO2, Li2O2 and other materials. The lithium replenisher is added in the preparation of the positive electrode material to make up for the efficiency loss of the negative electrode during the first charge and discharge. Taking the positive electrode active material as lithium iron phosphate (LFP) and the lithium replenisher as Li5FeO4 as an example, its mechanism of action is: during the first charge process, the lithium replenisher will release a specific capacity of >600mAh / g, and the first discharge capacity is generally 30mAh / g~40mAh / g. It produces excess lithium ions to supplement the lithium loss of the first efficiency of the graphite negative electrode and releases oxygen. The lithium supplement Li5FeO4 has two charging platforms during the first charging process, which are about 3.5V~3.6V and 3.9V~4.0V respectively. Li5FeO4 will undergo a lithium removal reaction at each platform, and will eventually generate LiFeO2 and O2; moreover, the lithium supplement generally needs to be charged to a higher voltage (>4.0V) to exert the maximum lithium supplement effect of the lithium supplement. This voltage is higher than the conventional voltage range of lithium iron phosphate (LFP) (about 2.0V~3.75V). Therefore, under the high voltage range, some other gases or irreversible gas production are generated. The sources of gas production include: on the one hand, the decomposition and oxygen release of the lithium supplement under high voltage, and on the other hand, the lithium removal products of the lithium supplement catalyze the decomposition of the electrolyte to produce gas under high voltage.
[0048] In the prior art, stable materials are used as additives or coating layers of lithium supplements to inhibit decomposition and gas production of electrolytes or eliminate oxygen, but the effect of reducing gas production is not obvious.
[0049] To this end, a first aspect of an embodiment of the present application proposes a lithium supplement, comprising: a core, the core comprising a lithium-rich material; a coating layer, the coating layer coating the outside of the core, the coating layer comprising an oxygen-deficient compound.
[0050] "Oxygen-deficient compounds" generally refer to compounds in which the oxygen content in the material is lower than its stoichiometric ratio. For example, in some compound materials, due to the influence of production process, heat treatment or chemical environment, the oxygen atoms in the lattice may be partially missing, forming oxygen vacancies. Therefore, the valence state of the metal cations in it will be lower than the stable state, and it has a certain reducibility.
[0051] As a lithium supplement material, the lithium-rich material will release a large amount of oxygen during the electrochemical reaction process, resulting in excessive gas production during the formation stage. The residual active oxygen in the system after formation will continuously catalyze the decomposition of the electrolyte to produce gas during the high-temperature storage stage, and may even cause the battery valve to burst, resulting in serious safety accidents. Therefore, the embodiments of the present application propose to add a reducing anoxic compound to the coating layer of the lithium supplement agent. During the formation process of the lithium-supplemented battery core, the released oxygen can be evacuated by the negative pressure process. The residual active oxygen in the system will be consumed by the anoxic compound in the coating layer during the subsequent high-temperature storage stage. This is because the anoxic compound has a stronger reducing property than the electrolyte and can compete with the electrolyte and capture catalytic factors such as active oxygen in the system at a higher temperature, thereby reducing the catalytic decomposition of the electrolyte to produce gas.
[0052] In some embodiments of the present application, the anoxic compound includes at least one of an anoxic metal compound and an anoxic non-metal compound.
[0053] The anoxic compound selected in the embodiments of the present application has a stronger reducing property than the components of the electrolyte and can consume active catalytic factors such as active oxygen generated by the lithium supplement agent during the formation stage and the high-temperature storage stage, thereby reducing the side reaction between the electrolyte and the lithium supplement agent and further reducing the gas production.
[0054] "Anoxic metal compound" generally refers to a compound in which the oxygen content in the metal compound is lower than its stoichiometric ratio. For example, in some oxide materials, due to the influence of production process, heat treatment or chemical environment, some oxygen atoms in the crystal lattice may be missing, forming oxygen vacancies.
[0055] "Anoxic non-metal compound" generally refers to a situation in which oxygen vacancies are formed in the crystal lattice of a non-metal compound due to the oxygen content being lower than its stoichiometric ratio.
[0056] In some embodiments of the present application, the anoxic metal compound includes at least one of Al2O 3-x , MgO 1-y and TiO 2-z ; where 0 < x < 3, 0 < y < 1, 0 < z < 2; and / or, the anoxic non-metal compound includes SiO 2-a ; where 0 < a < 2.
[0057] The anoxic metal compound includes at least one of Al2O 3-x , MgO 1-y and TiO 2-z ; where 0 < x < 3, 0 < y < 1, 0 < z < 2. In a specific example, Al2O 3-xAmong them, x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 2.95, etc., or x is any integer or decimal between 0 and 3. In a specific example, MgO 1-y Among them, y can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, etc., or y is any integer or decimal between 0 and 1. In a specific example, TiO 2-z Among them, z can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 1.95, etc., or y is any integer or decimal between 0 and 2.
[0058] The oxygen-deficient metal oxides include Al2O 3-x , MgO 1-y and TiO 2-z At least one of them. These oxygen-deficient metal oxides have a lower cost; and because the relative molecular weights of these oxygen-deficient metal oxides are smaller, for the oxygen-deficient compounds of the same mass, there are more oxygen vacancies. Therefore, when the coating material of the lithium supplement agent is applied to the battery, it shows a good effect of consuming oxygen.
[0059] The oxygen-deficient non-metal compounds include SiO 2-a ; where 0 < a < 2. In a specific example, SiO 2-a Among them, a can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 1.95, etc., or a is any integer or decimal between 0 and 2.
[0060] In some embodiments of the present application, the oxygen-deficient compound is Al2O 3-x , MgO 1-y and TiO 2-z At least one of them.
[0061] In the embodiments of the present application, the oxygen-deficient metal oxide is Al2O 3-x , MgO 1-y and TiO 2-zAt least one of these oxygen-deficient metal oxides has a relatively low cost; and since the relative molecular mass of these oxygen-deficient metal oxides is small, for the same mass of oxygen-deficient compounds, there are more oxygen vacancies. Therefore, when the coating material of the lithium supplement agent is applied to the battery, the effect of consuming oxygen is better.
[0062] In some embodiments of the present application, the oxygen-deficient compound is Al2O 3-x , MgO 1-y and TiO 2-z At least one of them, and 0 < x < 1, 0 < y < 0.5, 0 < z < 1.
[0063] In the embodiments of the present application, at least one of the above three is selected as the oxygen-deficient compound, and the oxygen content is lower than its stoichiometric ratio. Therefore, the stability of these oxygen-deficient compounds is relatively high, the acquisition difficulty is relatively low, and the total cost is relatively low.
[0064] In some embodiments of the present application, the oxygen-deficient oxide can be a commercial product, and / or the oxygen-deficient metal oxide can be prepared by a method including annealing treatment.
[0065] The oxygen-deficient metal oxide is prepared by mixing a metal oxide in a stable valence state with a reducing agent and then performing annealing treatment. The reducing agent includes a metal element, a carbon material or other reducing agents.
[0066] In some embodiments of the present application, the preparation method of the oxygen-deficient metal oxide Al2O 3-x (0 < x < 3) includes:
[0067] Mix alumina and aluminum element according to the stoichiometric ratio, grind them, and then perform annealing treatment. The cooling system is furnace cooling to obtain the oxygen-deficient metal oxide Al2O 3-x (0 < x < 3).
[0068] Among them, the control parameters include at least one of the following:
[0069] The annealing temperature is 300°C to 800°C; further, the annealing temperature is 300°C to 600°C;
[0070] The annealing time is 2h to 10h; further, the annealing time is 2h to 5h;
[0071] The heating rate is 2°C / min to 10°C / min; further, the heating rate is 3°C / min to 5°C / min;
[0072] In some embodiments of the present application, the preparation method of the oxygen-deficient metal oxide MgO 1-y (0 < y < 1) includes:
[0073] Mix magnesium oxide and magnesium metal in a stoichiometric ratio, grind them, then perform annealing treatment with the cooling regime of furnace cooling to obtain oxygen-deficient metal oxide MgO 1-y (0 < y < 1).
[0074] Among them, the control parameters include at least one of the following:
[0075] The annealing temperature is 300°C to 800°C; further, the annealing temperature is 300°C to 600°C;
[0076] The annealing time is 2h to 10h; further, the annealing time is 2h to 5h;
[0077] The heating rate is 2°C / min to 10°C / min; further, the heating rate is 3°C / min to 5°C / min.
[0078] In some embodiments of the present application, the preparation method of oxygen-deficient metal oxide TiO 2-z (0 < z < 2) includes:
[0079] Mix titanium dioxide and titanium metal in a stoichiometric ratio, grind them, then perform annealing treatment with the cooling regime of furnace cooling to obtain oxygen-deficient metal oxide TiO 2-z (0 < z < 2).
[0080] Among them, the control parameters include at least one of the following:
[0081] The annealing temperature is 300°C to 800°C; further, 300°C to 600°C;
[0082] The annealing time is 2h to 10h; further, the annealing time is 2h to 5h;
[0083] The heating rate is 2°C / min to 10°C / min; further, 3°C / min to 5°C / min.
[0084] In some embodiments of the present application, based on the lithium-rich material, the mass percentage content m1 of the oxygen-deficient compound satisfies: 0<m1≤10%. In a specific example, the mass percentage content m1 of the oxygen-deficient compound is 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% , 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4. 7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7. 4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10%, etc.
[0085] In the embodiment of the present application, based on the lithium-rich material, the mass percentage content m1 of the oxygen-deficient compound meets the above conditions, which is beneficial to increase the energy of oxygen consumption and improve the effect of reducing gas production; at the same time, it can avoid adding too much lithium to supplement the lithium-rich material in the core, so that the battery can show good battery capacity.
[0086] In some embodiments of the present application, based on the lithium-rich material, the mass percentage content m1 of the oxygen-deficient compound satisfies: 0.1%<m1≤5%.
[0087] In the embodiment of the present application, based on the lithium-rich material, the mass percentage content m1 of the oxygen-deficient compound meets the above conditions, which is beneficial to increase the energy consumed by oxygen and improve the effect of reducing gas production; at the same time, it does not affect the lithium replenishment effect of the core lithium-rich material, and the battery exhibits good battery capacity.
[0088] In some embodiments of the present application, the D50 of the oxygen-deficient compound is 20 nm to 200 nm; and / or the D50 of the lithium-rich material is 50 1μm~20μm.
[0089] In the embodiment of the present application, the D50 of the anoxic compound refers to the statistical average of the particle sizes of all particles in the anoxic compound particle group. In a specific example, the D50 of the anoxic compound is 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, etc.
[0090] In the embodiment of the present application, the D50 of the oxygen-deficient compound meets the above conditions. Due to the smaller particle size, the better the dispersion during the process of the coated lithium supplement agent in the embodiment of the present application, the better the formation of a coating layer with a better density, thereby improving the structural stability of the coating layer. Moreover, the oxygen-deficient compound with a smaller particle size has a larger specific surface area as the coating layer material, which is conducive to the adsorption of active oxygen and improves the effect of oxygen consumption.
[0091] Furthermore, the D50 of the oxygen-deficient compound is 20nm to 50nm. In a specific example, the D50 of the oxygen-deficient compound is 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, etc.
[0092] In the present application, D of the lithium-rich material 50 is the particle size distribution parameter, which indicates the particle size corresponding to 50% of the cumulative distribution of particle size in lithium-rich materials. 50 It means that among a group of particles with a particle size distribution, 50% of the particles have a particle size less than or equal to this value, and the other 50% of the particles have a particle size greater than or equal to this value. 50 It is also called the median diameter or median particle size, which is often used to approximate the average particle size of a sample. 50 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 10μm, etc.
[0093] In the present application, D of the lithium-rich material 50When the above conditions are met, the lithium-rich material is used as a lithium supplement material in batteries because the particle size is relatively small. The smaller the degree of cracking of the particles, the smaller the interface area exposed to the electrolyte, and the less gas production may be, which is beneficial to improving battery performance.
[0094] Furthermore, the D of lithium-rich materials 50 It is 10μm~14μm.
[0095] In some embodiments of the present application, the lithium-rich material includes a binary lithium compound or a ternary lithium compound.
[0096] The lithium-rich material provided in the embodiment of the present application as a lithium supplement material can be a common material used for lithium supplementation in the art. In a specific example, the lithium-rich material includes a binary lithium compound or a ternary lithium compound.
[0097] Further, the binary lithium compound includes at least one of lithium oxide (Li2O) and lithium peroxide (Li2O2).
[0098] Further, the ternary lithium compound includes at least one of lithium hexacobaltate (Li6CoO4), lithium ferrate (Li5FeO4), lithium dinickelate (Li2NiO2) and lithium silicate (Li2SiO3).
[0099] In some embodiments of the present application, the lithium-rich material includes at least one of Li5FeO4, Li2NiO2, Li2O2 and.
[0100] In the embodiments of the present application, at least one of Li5FeO4, Li2NiO2, Li2O2 and is selected as a lithium-rich material, i.e., a lithium-supplementing material. The voltage platform of these lithium-rich materials matches the commonly used positive electrode materials, has a low cost, and has good environmental stability.
[0101] In some embodiments of the present application, the lithium-rich material may be a commercial product and / or may be prepared by a solid phase method.
[0102] The lithium source or the lithium source and the non-lithium metal source (such as iron source, nickel source, etc.) are mixed and ground, and then subjected to high-temperature solid-phase reaction and furnace cooling to synthesize the corresponding lithium-rich materials (such as Li5FeO4, Li2NiO2, Li2O2, etc.).
[0103] Further, the lithium source includes lithium hydroxide and / or lithium oxide; the non-lithium metal source includes hydroxide and / or oxide of the corresponding metal.
[0104] Furthermore, the control parameters include at least one of the following:
[0105] The sintering temperature is 500°C to 1000°C; further, the sintering temperature is 700°C to 900°C;
[0106] The sintering time is 6h to 15h; further, the sintering time is 7h to 12h;
[0107] The heating rate is 3°C / min to 10°C / min; further, the heating rate is 4°C / min to 7°C / min.
[0108] In some embodiments of the present application, the coating layer further includes a conductive material; the conductive material includes at least one of a conductive carbon material and a conductive non-carbon material.
[0109] The lithium-rich material in the lithium supplement has a large band gap and poor intrinsic electronic conductivity. The good conductivity provided by the conductive material in the lithium-rich material coating layer can improve the electrical properties of the lithium-rich material, so that it can give full play to its excellent lithium supplement properties during actual use.
[0110] In some embodiments of the present application, the conductive carbon material includes an organic conductive carbon material and / or an inorganic conductive carbon material.
[0111] Furthermore, the inorganic conductive carbon material includes at least one of carbon black, graphene, carbon nanotubes, fullerenes and amorphous carbon. The amorphous carbon is obtained by carbonizing precursor materials such as glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, polyaniline, anthracene and aniline.
[0112] Furthermore, the organic conductive carbon material includes at least one of carbon materials such as polypyrrole, polyaniline, polyethylene glycol, anthracene and aniline.
[0113] In some embodiments of the present application, the conductive material is at least one of carbon black, graphene, carbon nanotubes and fullerene.
[0114] In some embodiments of the present application, the conductive non-carbon material includes at least one of silver and copper.
[0115] In some embodiments of the present application, the water contact angle of the conductive material is 90°≤θ≤160°. When the water contact angle of the conductive material is within the above range, the conductive material has hydrophobicity, which can improve the environmental stability of the lithium supplement. The water contact angle of conductive carbon black is 100°≤θ≤150°, which has good hydrophobicity.
[0116] Since lithium-rich materials are prone to deterioration when encountering water and carbon dioxide in the environment, the lithium supplementation effect is affected. In this embodiment, the coating layer coated on the surface of the inner core of the lithium-rich material contains a hydrophobic conductive material, which is conducive to better separating the lithium-rich material from the environment, preventing the lithium-rich material from reacting with moisture and carbon dioxide in the environment, and protecting the lithium-rich material. In the specific example, the conductive material is carbon black.
[0117] In some embodiments of the present application, based on the lithium-rich material, the mass percentage content m2 of the conductive material satisfies: 0<m2≤10%. In a specific example, based on the lithium-rich material, the mass percentage content m2 of the conductive material is 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1 .9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6 %, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10%, etc.
[0118] In the embodiment of the present application, based on the lithium-rich material, the mass percentage content m2 of the conductive material meets the above conditions, which is beneficial to increase the conductivity of the lithium supplement.
[0119] In some embodiments of the present application, based on the lithium-rich material, the mass percentage content m2 of the conductive material satisfies: 0<m2≤5%.
[0120] In the embodiment of the present application, based on the lithium-rich material, the mass percentage content m2 of the conductive material meets the above conditions, which is beneficial to increase the conductivity of the lithium supplement agent, obtain a better coating effect, and have good hydrophobicity.
[0121] The second aspect of the embodiment of the present application provides a method for preparing a lithium supplement, comprising:
[0122] The lithium-rich material and the oxygen-deficient compound are mixed to obtain a mixture, and the mixture is subjected to heat treatment to obtain a lithium supplement.
[0123] The raw materials described in the embodiments may be directly "lithium-rich materials" and "oxygen-deficient compounds"; they may also refer to raw materials for preparing "lithium-rich materials" and raw materials for preparing "oxygen-deficient compounds".
[0124] The preparation method of the lithium supplement provided in the embodiment of the present application can be prepared by mixing, which is simple to operate and low in cost. The lithium supplement prepared in the embodiment of the present application contains an oxygen-deficient compound in the coating layer, which has a stronger reducing property than the electrolyte components, and can consume the active catalytic factors such as active oxygen generated by the lithium supplement in the formation stage and the high-temperature storage stage, thereby reducing the side reactions between the electrolyte and the lithium supplement, and further reducing the gas production.
[0125] In some embodiments of the present application, the step of mixing the lithium-rich material and the oxygen-deficient compound to obtain a mixture further includes adding a conductive material.
[0126] The lithium-rich material, the oxygen-deficient compound and the conductive material are mixed to obtain a mixture, and the mixture is subjected to heat treatment to obtain a lithium supplement agent.
[0127] The lithium-rich material in the lithium supplement has a large band gap and poor intrinsic electronic conductivity. By adding conductive materials, both the conductive materials and the oxygen-deficient compounds are used to form a coating layer, which provides good conductivity and can improve the electrical properties of the lithium-rich material, so that it can give full play to its excellent lithium supplement properties during actual use.
[0128] The conductive material includes at least one of a conductive carbon material and a conductive non-carbon material.
[0129] In some embodiments of the present application, the step of mixing the raw materials of lithium-rich material and oxygen-deficient compound comprises a physical-mechanical mixing method; or, the step of mixing the lithium-rich material, oxygen-deficient compound and conductive material to obtain a mixture comprises a physical-mechanical mixing method.
[0130] In the embodiments of the present application, the raw materials are mixed by adopting a method including a physical mechanical mixing method, so that the lithium-rich material and the oxygen-deficient compound are in full contact, and a coating layer containing the oxygen-deficient compound is formed on the surface of the lithium-rich material.
[0131] Furthermore, during the physical mechanical mixing method, the mixing time is controlled to be 2 hours to 8 hours.
[0132] In some embodiments of the present application, raw materials including lithium-rich materials and oxygen-deficient compounds are mixed and heat treated to further control the heat treatment; the heat treatment control parameters include: the heat treatment temperature is 20°C to 200°C, and / or the heat treatment time is 1h to 6h.
[0133] In the embodiment of the present application, the raw materials are mixed and then heat treated to prepare the lithium supplement. The heat treatment is conducive to promoting the bonding between the oxygen-deficient compound and the lithium-rich material contact interface, improving the bonding strength between the coating layer and the core, thereby improving the structural stability of the lithium supplement, and protecting the lithium-rich material from contact and deterioration with water and carbon dioxide in the environment, thereby improving battery performance. This is because, under the heat treatment conditions,
[0134] The oxygen-deficient compound has lattice defects and can easily form bonds with the transition metal in the lithium-rich material, which is beneficial to improving the bonding strength. The lattice oxygen of the lithium-rich material occupies the oxidation vacancies of the oxygen-deficient compound, which can also improve the bonding strength.
[0135] In some embodiments of the present application, the anoxic compound is prepared by the following method:
[0136] The metal oxide or non-metal oxide is mixed with a reducing agent and subjected to annealing to obtain an oxygen-deficient compound; wherein the annealing parameters include at least one of the following:
[0137] (a) Annealing temperature is 500°C to 1000°C;
[0138] (b) Annealing time is 6h to 15h;
[0139] (c) Annealing is performed under an inert atmosphere.
[0140] The oxygen-deficient metal oxide is prepared by mixing a metal oxide in a stable valence state with a metal element and then performing annealing treatment.
[0141] The above-mentioned "reducing agent" can reduce part of the metal from a high valence state to a low valence state when mixed with a metal oxide to prepare an oxygen-deficient metal compound; and can reduce part of the non-metal from a high valence state to a low valence state when mixed with a non-metal oxide to prepare an oxygen-deficient non-metal compound. The reducing agent can be a reducing agent commonly used in the art.
[0142] Furthermore, in the step of preparing the oxygen-deficient metal compound, the reducing agent used includes the corresponding metal element, that is, the metal oxide is mixed with the corresponding metal element, and the oxygen-deficient metal compound is obtained by annealing.
[0143] Furthermore, in the step of preparing the oxygen-deficient non-metallic compound, the reducing agent used includes the corresponding non-metallic element, that is, the non-metallic oxide is mixed with the corresponding non-metallic element, and the oxygen-deficient non-metallic compound is obtained by annealing.
[0144] In some embodiments of the present application, the preparation method of the oxygen-deficient metal oxide Al2O 3-x (0 < x < 3) includes:
[0145] Mix alumina and aluminum in accordance with the stoichiometric ratio and grind them, then perform annealing treatment, and the cooling system is furnace cooling to obtain the oxygen-deficient metal oxide Al2O 3-x (0 < x < 3).
[0146] Among them, the control parameters include at least one of the following:
[0147] The annealing temperature is 300°C to 800°C; further, the annealing temperature is 300°C to 600°C;
[0148] The annealing time is 2 h to 10 h; further, the annealing time is 2 h to 5 h;
[0149] The heating rate is 2°C / min to 10°C / min; further, the heating rate is 3°C / min to 5°C / min;
[0150] In some embodiments of the present application, the preparation method of the oxygen-deficient metal oxide MgO 1-y (0 < y < 1) includes:
[0151] Mix magnesium oxide and magnesium in accordance with the stoichiometric ratio and grind them, then perform annealing treatment, and the cooling system is furnace cooling to obtain the oxygen-deficient metal oxide MgO 1-y (0 < y < 1).
[0152] Among them, the control parameters include at least one of the following:
[0153] The annealing temperature is 300°C to 800°C; further, the annealing temperature is 300°C to 600°C;
[0154] The annealing time is 2 h to 10 h; further, the annealing time is 2 h to 5 h;
[0155] The heating rate is 2°C / min to 10°C / min; further, the heating rate is 3°C / min to 5°C / min.
[0156] In some embodiments of the present application, the preparation method of the oxygen-deficient metal oxide TiO 2-z (0 < z < 2) includes:
[0157] Mix titanium dioxide and titanium in accordance with the stoichiometric ratio and grind them, then perform annealing treatment, and the cooling system is furnace cooling to obtain the oxygen-deficient metal oxide TiO 2-z (0 < z < 2).
[0158] The control parameters include at least one of the following:
[0159] The annealing temperature is 300°C to 800°C; further, 300°C to 600°C;
[0160] The annealing time is 2h to 10h; further, the annealing time is 2h to 5h;
[0161] The heating rate is 2°C / min to 10°C / min; further, 3°C / min to 5°C / min.
[0162] A third aspect of the embodiments of the present application provides a positive electrode plate, comprising the above-mentioned lithium supplement agent, or the lithium supplement agent obtained by the above-mentioned preparation method.
[0163] The positive electrode plate provided in the embodiment of the present application, comprising the above-mentioned lithium replenishing agent, exhibits a good lithium replenishing effect and is beneficial to reducing gas production.
[0164] In some embodiments of the present application, the positive electrode active material may adopt the positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) or at least one of its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, or a composite material of lithium iron manganese phosphate and carbon.
[0165] In some embodiments of the present application, the positive electrode active material includes LiFePO4 and LiNi c Co d Mn 1-c-d O2, wherein at least one of 0.3≤c<1, 0≤d≤0.5.
[0166] In some embodiments of the present application, the positive electrode sheet further includes a positive electrode current collector.
[0167] Further, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0168] In some embodiments of the present application, the positive electrode plate further includes a positive electrode active material layer, which is located on at least one side of the positive electrode collector; the positive electrode active material layer includes a positive electrode active material and a lithium supplement.
[0169] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0170] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0171] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, lithium supplement, conductive agent, binder) are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0172] The features and advantages described above for the lithium supplement of the first aspect of the present application are also applicable to the positive electrode plate of the third aspect of the present application and will not be described in detail here.
[0173] A fourth aspect of the embodiments of the present application provides a battery, comprising the above-mentioned positive electrode plate.
[0174] The battery provided in the embodiment of the present application includes the above-mentioned positive electrode plate and produces less gas.
[0175] In some embodiments of the present application, the battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0176] In some embodiments of the present application, the battery may include an outer package for packaging the positive electrode sheet, the negative electrode sheet, and the electrolyte.
[0177] In some embodiments of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.
[0178] In some embodiments of the present application, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.
[0179] The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0180] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0181] A fifth aspect of the embodiments of the present application provides an electrical device, comprising the above-mentioned battery.
[0182] The electrical equipment in the embodiments of the present application has good safety performance.
[0183] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.
[0184] As an electrical device, a battery cell, battery module or battery pack can be selected according to its usage requirements.
[0185] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.
[0186] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0187] It should be noted that the features and advantages described above for the lithium supplement of the first aspect of the present application are also applicable to the battery of the fourth aspect and the electrical equipment of the fifth aspect of the present application, and will not be repeated here.
[0188] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0189] Example 1
[0190] Step 1: Preparation of lithium supplement materials:
[0191] The lithium source and the iron source are mixed and ground according to a stoichiometric ratio (molar ratio of 10:1) to obtain a mixture; wherein the lithium source and the iron source are lithium hydroxide and iron oxide, respectively.
[0192] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 700°C, and an annealing time of 12h, and then ground after cooling to room temperature with the furnace, with a grinding power of 50kw. The positive electrode lithium supplement material Li5FeO4 powder sample was obtained, with a D50 of 12μm.
[0193] Step 2: Preparation of oxygen-deficient non-lithium metal oxides:
[0194] Alumina and aluminum were mixed and ground according to a stoichiometric ratio (molar ratio 7:1) at a grinding power of 20 kW to obtain a mixture.
[0195] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, an annealing time of 5h, and an annealing environment of inert atmosphere. After that, it was cooled to room temperature with the furnace and then ground with a grinding power of 80kw to obtain oxygen-deficient non-lithium metal oxide, namely oxygen-deficient aluminum oxide Al2O 2.8 Powder sample, D50 is 50nm.
[0196] Step 3: Prepare conductive carbon material:
[0197] Carbon black is used as the conductive carbon material.
[0198] Step 4: Preparation of lithium supplement:
[0199] Physical and mechanical mixing method: Li5FeO4 and Al2O 2.8 After being uniformly mixed with the conductive carbon material in a mass ratio of 98:1:1, heat treatment is carried out at 150°C for 5 hours to obtain a lithium supplement agent, which is named "Example 1". The order of the first step, the second step, and the third step above can be interchanged.
[0200] Example 2
[0201] The difference between this embodiment and embodiment 1 is that in the fourth step, Li5FeO4, Al2O 2.8 , the conductive carbon materials are uniformly mixed in a mass ratio of 97:2:1, and then heat treated at 150° C. for 5 hours to obtain a lithium supplement, which is named “Example 2”.
[0202] Example 3
[0203] The difference between this embodiment and embodiment 1 is that:
[0204] Step 2: Preparation of oxygen-deficient non-lithium metal oxides:
[0205] Magnesium oxide and magnesium element are mixed and ground according to a stoichiometric ratio (molar ratio 4:1) at a grinding power of 20 kW to obtain a mixture.
[0206] The obtained mixture is subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, and an annealing time of 5h. After cooling to room temperature with the furnace, it is ground with a grinding power of 88kw to obtain an oxygen-deficient non-lithium metal oxide, namely, an oxygen-deficient aluminum oxide MgO. 0.8 Powder sample, D50 is 50nm.
[0207] Step 3: Prepare conductive carbon material:
[0208] Carbon black is used as the conductive carbon material.
[0209] Step 4: Preparation of lithium supplement:
[0210] Physical and mechanical mixing method: Li5FeO4 and MgO 0.8 After being uniformly mixed with the conductive carbon material in a mass ratio of 98:1:1, heat treatment is performed at 150° C. for 5 hours to obtain a lithium supplement agent, which is named “Example 3”.
[0211] Example 4
[0212] The difference between this embodiment and embodiment 3 is that:
[0213] The fourth step is to mix Li5FeO4 and MgO 0.8 , the conductive carbon material is uniformly mixed in a mass ratio of 97:2:1, and then heat-treated at 150° C. for 5 hours to obtain a lithium supplement, which is named “Example 4”.
[0214] Example 5
[0215] The difference between this embodiment and embodiment 1 is that:
[0216] Step 2: Preparation of oxygen-deficient non-lithium metal oxides:
[0217] Titanium oxide and titanium element were mixed and ground according to a stoichiometric ratio (molar ratio 9:1) at a grinding power of 15 kW to obtain a mixture.
[0218] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, and an annealing time of 5h. After cooling to room temperature with the furnace, it was ground with a grinding power of 90kw. The oxygen-deficient non-lithium metal oxide, namely oxygen-deficient aluminum oxide TiO 1.8 Powder sample, D50 is 50nm.
[0219] Step 3: Prepare conductive carbon material:
[0220] Carbon black is used as the conductive carbon material.
[0221] Step 4: Preparation of lithium supplement:
[0222] Physical and mechanical mixing method: Li5FeO4 and TiO 1.8 After being uniformly mixed with the conductive carbon material in a mass ratio of 98:1:1, heat treatment is performed at 150° C. for 5 hours to obtain a lithium supplement agent, which is named “Example 5”.
[0223] Example 6
[0224] The difference between this embodiment and embodiment 3 is that:
[0225] The fourth step is to mix Li5FeO4 and TiO 1.8 , the conductive carbon materials are uniformly mixed at a mass ratio of 97:2:1 at room temperature 20°C, and then heat treated at 150°C for 5 hours to obtain a lithium supplement, which is named "Example 6".
[0226] Example 7
[0227] The difference between this embodiment and embodiment 1 is that:
[0228] Step 2: Preparation of oxygen-deficient non-lithium metal oxides:
[0229] Alumina and aluminum were mixed and ground according to a stoichiometric ratio (molar ratio 2.5:1) at a grinding power of 20 kW to obtain a mixture.
[0230] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, and an annealing time of 5h. After cooling to room temperature with the furnace, it was ground with a grinding power of 80kw to obtain oxygen-deficient non-lithium metal oxide, namely oxygen-deficient aluminum oxide Al2O 2.5 Powder sample, D50 is 50nm.
[0231] A lithium supplement was obtained and named "Example 7".
[0232] Example 8
[0233] The difference between this embodiment and embodiment 1 is that:
[0234] Step 2: Preparation of oxygen-deficient non-lithium metal oxides:
[0235] Alumina and aluminum were mixed and ground according to a stoichiometric ratio (molar ratio 1.64:1) at a grinding power of 20 kW to obtain a mixture.
[0236] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, and an annealing time of 5h. After cooling to room temperature with the furnace, it was ground with a grinding power of 80kw to obtain oxygen-deficient non-lithium metal oxide, namely oxygen-deficient aluminum oxide Al2O 2.3 Powder sample, D50 is 50nm.
[0237] A lithium supplement was obtained and named "Example 8".
[0238] Example 9
[0239] The difference between this embodiment and embodiment 1 is that:
[0240] The fourth step is to mix Li5FeO4 and Al2O 2.8 , the conductive carbon materials are uniformly mixed in a mass ratio of 98.9:0.1:1, and then heat treated at 150° C. for 5 hours to obtain a lithium supplement, which is named “Example 9”.
[0241] Example 10
[0242] The difference between this embodiment and embodiment 1 is that:
[0243] The fourth step is to mix Li5FeO4 and Al2O 2.8 , the conductive carbon materials are uniformly mixed in a mass ratio of 97.5:1.5:1, and then heat treated at 150° C. for 5 hours to obtain a lithium supplement, which is named “Example 10”.
[0244] Embodiment 11
[0245] The difference between this embodiment and embodiment 1 is that:
[0246] The fourth step is to mix Li5FeO4 and Al2O 2.8 , and the conductive carbon materials are uniformly mixed in a mass ratio of 96:3:1, and then heat-treated at 150° C. for 5 hours to obtain a lithium supplement, which is named “Example 11”.
[0247] Example 12
[0248] The difference between this embodiment and embodiment 1 is that:
[0249] The fourth step is to mix Li5FeO4 and Al2O 2.8 , and the conductive carbon material are uniformly mixed in a mass ratio of 94:5:1, and then heat-treated at 150° C. for 5 hours to obtain a lithium supplement, which is named “Example 12”.
[0250] Example 13
[0251] The difference between this embodiment and embodiment 1 is that:
[0252] The fourth step is to mix Li5FeO4 and Al2O 2.8 , and the conductive carbon materials are uniformly mixed in a mass ratio of 89:10:1, and then heat treated at 150° C. for 5 hours to obtain a lithium supplement, which is named “Example 13”.
[0253] Embodiment 14
[0254] The difference between this embodiment and embodiment 1 is that:
[0255] The fourth step is to mix Li5FeO4 and Al2O 2.8 , the conductive carbon materials are uniformly mixed in a mass ratio of 88.5:10.5:1, and then heat treated at 150° C. for 5 hours to obtain a lithium supplement, which is named “Example 14”.
[0256] Embodiment 15
[0257] The difference between this embodiment and embodiment 1 is that:
[0258] Step 2: Preparation of oxygen-deficient non-lithium metal oxides:
[0259] Alumina and aluminum were mixed and ground according to a stoichiometric ratio (molar ratio 7:1) at a grinding power of 18 kW to obtain a mixture.
[0260] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, and an annealing time of 5h. After cooling to room temperature with the furnace, it was ground with a grinding power of 150kw to obtain oxygen-deficient non-lithium metal oxide, namely oxygen-deficient aluminum oxide Al2O 2.8 Powder sample, D50 is 20nm.
[0261] A lithium supplement was obtained and named "Example 15".
[0262] Example 16
[0263] The difference between this embodiment and embodiment 1 is that:
[0264] Step 2: Preparation of oxygen-deficient non-lithium metal oxides:
[0265] Alumina and aluminum were mixed and ground according to a stoichiometric ratio (molar ratio 7:1) at a grinding power of 15 kW to obtain a mixture.
[0266] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, and an annealing time of 5h. After cooling to room temperature with the furnace, it was ground with a grinding power of 60kw to obtain oxygen-deficient non-lithium metal oxide, namely oxygen-deficient aluminum oxide Al2O 2.8 Powder sample, D50 is 150nm.
[0267] A lithium supplement was obtained and named "Example 16".
[0268] Embodiment 17
[0269] The difference between this embodiment and embodiment 1 is that:
[0270] Step 2: Preparation of oxygen-deficient non-lithium metal oxides:
[0271] Alumina and aluminum were mixed and ground according to a stoichiometric ratio (molar ratio 7:1) at a grinding power of 15 kW to obtain a mixture.
[0272] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, and an annealing time of 5h. After cooling to room temperature with the furnace, it was ground with a grinding power of 50kw to obtain oxygen-deficient non-lithium metal oxide, namely oxygen-deficient aluminum oxide Al2O 2.8 Powder sample, D50 is 200nm.
[0273] A lithium supplement was obtained and named "Example 17".
[0274] Embodiment 18
[0275] The difference between this embodiment and embodiment 1 is that:
[0276] Step 2: Preparation of oxygen-deficient non-lithium non-metal oxides:
[0277] Silicon oxide and silicon element were mixed and ground according to a stoichiometric ratio (molar ratio 9:1) at a grinding power of 10 kW to obtain a mixture.
[0278] The obtained mixture was subjected to high temperature annealing treatment, with a heating rate of 6°C / min, an annealing temperature of 500°C, and an annealing time of 5h. After cooling to room temperature with the furnace, it was ground with a grinding power of 40kw to obtain oxygen-deficient non-lithium metal oxide, namely oxygen-deficient aluminum oxide SiO 1.8Powder sample, D50 is 50nm.
[0279] A lithium supplement was obtained and named "Example 18".
[0280] Embodiment 19
[0281] The difference between this embodiment and embodiment 1 is that:
[0282] The third step is to prepare the conductive material: polypyrrole is used as the conductive material.
[0283] A lithium supplement was obtained and named "Example 19".
[0284] Embodiment 20
[0285] The difference between this embodiment and embodiment 1 is that:
[0286] In the first step, Li2O2 is used as a lithium supplement with a D50 of 50nm.
[0287] A lithium supplement was obtained and named "Example 20".
[0288] Embodiment 21
[0289] The preparation methods of this embodiment are the same as those of embodiment 1, except that: the lithium supplement provided in embodiment 1 is used for lithium iron phosphate batteries (i.e., the positive electrode active material is lithium iron phosphate), and the lithium supplement prepared in this embodiment is used for 811 batteries (i.e., the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O2).
[0290] Embodiment 22
[0291] The difference between this embodiment and embodiment 1 is that:
[0292] The third step is to use Li5FeO4 and Al2O without using conductive materials. 2.8 The mixture was uniformly mixed at a mass ratio of 99:1 for 5 hours to obtain a modified lithium supplement material, which was named "Example 22".
[0293] Embodiment 23
[0294] The difference between this embodiment and embodiment 1 is that:
[0295] Step 4: Preparation of lithium supplement:
[0296] Physical and mechanical mixing method: Li5FeO4 and Al2O 2.8After being uniformly mixed with the conductive carbon material in a mass ratio of 98:1:1, heat treatment is carried out at 40°C for 5 hours to obtain a lithium supplement agent, which is named "Example 23".
[0297] Embodiment 24
[0298] The difference between this embodiment and embodiment 1 is that:
[0299] Step 4: Preparation of lithium supplement:
[0300] Physical and mechanical mixing method: Li5FeO4 and Al2O 2.8 After being uniformly mixed with the conductive carbon material in a mass ratio of 98:1:1, heat treatment is performed at 100°C for 5 hours to obtain a lithium supplement agent, which is named "Example 24".
[0301] Embodiment 25
[0302] The difference between this embodiment and embodiment 1 is that:
[0303] Step 4: Preparation of lithium supplement:
[0304] Physical and mechanical mixing method: Li5FeO4 and Al2O 2.8 After being uniformly mixed with the conductive carbon material in a mass ratio of 98:1:1, heat treatment is carried out at 200°C for 5 hours to obtain a lithium supplement agent, which is named "Example 25".
[0305] Comparative Example 1
[0306] The difference between Comparative Example 1 and Example 1 is that:
[0307] The second step is not carried out, that is, no oxygen-deficient aluminum oxide Al2O 2.8 Coating, after the obtained Li5FeO4 and the conductive carbon material are uniformly mixed in a mass ratio of 98:2, heat treatment is carried out at 150°C for 5 hours to obtain a lithium supplement agent, which is named "Comparative Example 1".
[0308] Comparative Example 2
[0309] The same method as in Example 1 is used, except that aluminum oxide Al2O3 is used to replace the oxygen-deficient compound (Al2O 2.8 ), and the other conditions remain unchanged.
[0310] Comparative Example 3
[0311] The same method as in Example 20 is used, except that:
[0312] The second step is not carried out, that is, no oxygen-deficient aluminum oxide Al2O2.8 Coating, after Li2O2 and conductive carbon material are uniformly mixed in a mass ratio of 98:2, heat treatment is carried out at 150°C for 5 hours to obtain a lithium supplement agent, which is named "Comparative Example 3".
[0313] Comparative Example 4
[0314] The same method as in Example 21 is used, except that aluminum oxide Al2O3 is used to replace the oxygen-deficient compound (Al2O 2.8 ), and the other conditions remain unchanged.
[0315] The D50 detection method of lithium supplement materials: using Malvern laser particle size analyzer for testing.
[0316] Detection method of D50 of oxygen-deficient compounds: using Malvern laser particle size analyzer for testing.
[0317] The mass percentage detection method of anoxic compounds is: controlled by weighing during feeding and ICP test is adopted at the finished product end.
[0318] Characterization method of the oxygen-deficient state of oxygen-deficient compounds: XPS test, characterizing the valence state of metal elements and oxygen.
[0319] The detection method of the mass percentage of the conductive material is as follows: the material is fed by weighing control, and the finished product is tested by elemental analysis or thermogravimetric auxiliary testing.
[0320] The test parameters are shown in Table 1.
[0321] Table 1
[0322]
[0323] Preparation example:
[0324] Preparation of positive electrode sheet: The lithium supplement material prepared by the above-mentioned Examples 1-20, Examples 22-25 and Comparative Examples 1-4 is mixed with the binder PVDF (polyvinylidene fluoride), the conductive agent CNT (carbon nanotube), NMP (N-methyl-2-pyrrolidone), LFP (lithium iron phosphate) to prepare a positive electrode slurry for coating, and the positive electrode sheet is prepared. Among them, the lithium supplement material accounts for 1%, the iron lithium material accounts for 90%, the binder accounts for 4%, and the conductive agent accounts for 5%.
[0325] Alternatively, the binder PVDF (polyvinylidene fluoride), the conductive agent CNT (carbon nanotube), NMP (N-methyl-2-pyrrolidone), NMC811 (LiNi 0.8 Co 0.1 Mn 0.1O2) The lithium supplement material prepared by the above-mentioned Example 21 and Comparative Example 4 is prepared into a positive electrode slurry for coating to prepare a positive electrode sheet, wherein the lithium supplement material accounts for 1%, the iron lithium material accounts for 90%, the binder accounts for 4%, and the conductive agent accounts for 5%.
[0326] Button test: punch the above positive electrode into small discs, assemble button batteries in a glove box, the glove box environment is: water <0.1ppm, oxygen <1ppm, the counter electrode is a lithium sheet, the electrolyte is an electrolyte composition of the solvent is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, the solute is 1.0 mol / L LiPF6, the assembled button battery is tested using the Blue Electric system to test the material specific capacity.
[0327] Preparation of full battery: Take the above positive electrode sheets and stack them in a Z-shaped pattern according to the alternation of negative electrode-diaphragm-positive electrode-diaphragm-negative electrode. Each battery cell contains 7 positive electrodes and 8 negative electrodes. Each battery cell is injected with 5.8g electrolyte. Then, the battery cell is subjected to chemical decomposition, aging and capacity separation. The negative electrode is made of graphite material, wherein the mass ratio of graphite, conductive carbon black and SBR (styrene-butadiene rubber) is 96:2:2.
[0328] Electrochemical performance test:
[0329] Positive electrode capacity test after lithium supplementation: Assemble the positive electrode and test it with a Xinwei battery cabinet. The first charge capacity in grams and discharge capacity in grams when the charging voltage is 2.5-4.3V and the charging current is 0.5C.
[0330] Lithium-replenishing battery cell gas production test
[0331] The lithium-supplemented battery cells assembled with the positive lithium-supplementing agents of the above-mentioned Examples 1-25 and Comparative Examples 1-4 were subjected to in-situ differential electrochemical mass spectrometry testing. The gas production during the first cycle charging process (formation stage) was detected, with a voltage window of 2.0V to 4.3V and a charging current of 0.1C. The battery was charged to 4.3V at a constant voltage, and after being stored at 60°C for 10 days, its gas production was tested.
[0332] The test results are shown in Table 2.
[0333] Table 2
[0334]
[0335] In summary, the lithium supplement provided in the embodiments of the present application can effectively alleviate gas production and improve the lithium supplement effect. Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A lithium supplement, characterized in that: include: a core, the core comprising a lithium-rich material; The coating layer is coated outside the inner core, and the coating layer includes an oxygen-deficient compound.
2. The lithium supplement according to claim 1, characterized in that: The oxygen-deficient compound includes at least one of an oxygen-deficient metal compound and an oxygen-deficient non-metal compound.
3. The lithium supplement according to claim 2, characterized in that: The oxygen-deficient metal compound includes Al2O 3-x MgO 1-y and TiO 2-z At least one of; wherein, 0 <x<3,0<y<1,0<z<2; And / or, the oxygen-deficient non-metallic compound comprises SiO 2-a ; Among them, 0 <a<2。 4. The lithium supplement according to any one of claims 1 to 3, characterized in that: Taking the lithium supplement as a reference, the mass percentage content m1 of the oxygen-deficient compound satisfies: 0<m1≤10%.
5. The lithium supplement according to any one of claims 1 to 4, characterized in that: Taking the lithium supplement as a reference, the mass percentage content m1 of the oxygen-deficient compound satisfies: 0.1%<m1≤5%.
6. The lithium supplement according to any one of claims 1 to 5, characterized in that: The D50 of the anoxic compound is 20nm to 200nm; And / or, D of the lithium-rich material 50 1μm~20μm.
7. The lithium supplement according to any one of claims 1 to 6, characterized in that: The lithium-rich material includes a binary lithium compound or a ternary lithium compound.
8. The lithium supplement according to any one of claims 1 to 7, characterized in that: The lithium-rich material includes at least one of Li5FeO4, Li2NiO2, Li2O2 and.
9. The lithium supplement according to any one of claims 1 to 8, characterized in that: The coating layer further comprises a conductive material; the conductive material comprises at least one of a conductive carbon material and a conductive non-carbon material.
10. The lithium supplement according to claim 9, characterized in that: The water contact angle of the conductive material is 90°≤θ≤160°.
11. The lithium supplement according to claim 9 or 10, characterized in that: Taking the lithium supplement as a reference, the mass percentage content m2 of the conductive material satisfies: 0<m2≤10%.
12. A method for preparing the lithium supplement according to any one of claims 1 to 11, characterized in that: include: The lithium-rich material and the oxygen-deficient compound are mixed to obtain a mixture, and the mixture is subjected to heat treatment to obtain the lithium supplement agent.
13. The preparation method according to claim 12, characterized in that: The step of mixing the lithium-rich material and the oxygen-deficient compound to obtain a mixture also includes adding a conductive material.
14. The preparation method according to claim 12 or 13, characterized in that: The heat treatment control parameters include: The heat treatment temperature is 20° C. to 200° C., and / or the heat treatment time is 1 h to 6 h.
15. The preparation method according to any one of claims 12 to 13, characterized in that: The anoxic compound is prepared by the following method: The metal oxide or non-metal oxide is mixed with a reducing agent, and the oxygen-deficient compound is obtained by annealing; wherein the annealing parameters include at least one of the following: (a) Annealing temperature is 500°C to 1000°C; (b) Annealing time is 6h to 15h; (c) Annealing is performed under an inert atmosphere.
16. A positive electrode plate, characterized in that: The lithium supplement comprises the lithium supplement according to any one of claims 1 to 11.
17. The positive electrode sheet according to claim 16, characterized in that: The positive electrode sheet also includes a positive electrode active material; the positive electrode active material includes LiFePO4 and LiNi c Co d Mn 1-c-d O2, wherein at least one of 0.3≤c<1, 0≤d≤0.
5.
18. A battery, characterized in that: Including the positive electrode sheet as described in claim 16 or 17.
19. An electrical equipment, characterized in that: Comprising the battery of claim 18.
Citation Information
Patent Citations
Double-layer coated positive electrode lithium supplementing material and lithium ion battery comprising same
CN113178568A
Positive electrode lithium supplementing material and lithium ion battery comprising same
CN113328079A
Positive pole piece of high-energy-density lithium ion battery, and preparation method and application thereof
CN113745460A
Lithium supplement additive and preparation method and application thereof
CN116525975A
Lithium supplement material and preparation method thereof, positive pole piece and secondary battery
CN116826205A
Cited By
Lithium-rich manganese-based oxide pre-lithiation additive, preparation method thereof and positive plate
CN122314866A
Positive electrode lithium-supplementing agent, preparation method therefor, positive electrode sheet, battery, and electrical device
WO2026092715A1